2018
DOI: 10.1590/1982-021620182040117
|View full text |Cite
|
Sign up to set email alerts
|

Workers of the hospital maintenance sector: protection, hearing symptoms and noise exposure

Abstract: Purpose: to investigate the use of hearing protection and symptoms in hospital maintenance workers and evaluate the noise level of the machines. Methods: a cross-sectional quantitative study held with workers from a public hospital maintenance service. A questionnaire related to personal, clinical and occupational history was used. Measurement of the noise level of the machines in the sector was carried out using a sound pressure level meter. Results: 57 male workers participated, mean age of 43.28 years, am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
2
0
2
Order By: Relevance
“…The present study demonstrated a higher prevalence of self-perception of decreased hearing among those who reported anxiety. Manifestations of anxiety, stress, irritability, insomnia, and difficulty concentrating are common symptoms caused by exposure to high sound pressure levels (8)(9)(10) . A study conducted in Canada by Bishop's University demonstrated that situational anxiety increases significantly when the individual is exposed to 75 dB of environmental noise (23) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study demonstrated a higher prevalence of self-perception of decreased hearing among those who reported anxiety. Manifestations of anxiety, stress, irritability, insomnia, and difficulty concentrating are common symptoms caused by exposure to high sound pressure levels (8)(9)(10) . A study conducted in Canada by Bishop's University demonstrated that situational anxiety increases significantly when the individual is exposed to 75 dB of environmental noise (23) .…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly reported auditory symptoms are tinnitus, otalgia, difficulty understanding speech, ear fullness, discomfort with intense sounds, and hearing loss. Symptoms such as headaches, insomnia, stress, irritability, fatigue, anxiety, inattention, and vision, memory, sleep, and mood disorders are also reported (8)(9)(10) .…”
Section: Introductionmentioning
confidence: 99%
“…O presente estudo demonstrou maior prevalência de autopercepção de diminuição da audição entre pessoas que referiram ansiedade. Manifestações de ansiedade, estresse, irritabilidade, insônia e dificuldade de concentração são sintomas comuns causados pela exposição a elevados níveis de pressão sonora (NPS) (8)(9)(10) . Estudo realizado no Canadá, pela Universidade de Bishop, demonstrou que a ansiedade situacional aumenta significativamente quando o indivíduo é exposto a 75 dB de ruído ambiental (23) .…”
Section: Discussionunclassified
“…Os sintomas auditivos mais comumente referidos são zumbido, otalgia, dificuldade de compreensão da fala, plenitude auricular, desconforto a sons intensos e perda auditiva. São relatados, ainda, sintomas como cefaleia, insônia, estresse, irritabilidade, fadiga, ansiedade, desatenção e distúrbios de visão, memória, sono e humor (8)(9)(10) .…”
Section: Introductionunclassified